Pathological identification of HER2-low breast cancer: Tips, tricks, and troubleshooting for the optimal test - Sajjadi, Elham; Guerini-Rocco, Elena; De Camilli, Elisa; Pala, Oriana; Mazzarol, Giovanni; Venetis, Konstantinos; Ivanova, Mariia; Fusco, Nicola (Frontiers in Molecular Biosciences, 2023)
The introduction of novel anti-HER2 antibody-drug conjugates (ADC) for the treatment of HER2-low breast cancers has transformed the traditional dichotomy of HER2 status to an expanded spectrum. However, the identification of HER2-low (i.e., immunohistochemistry (IHC) score 1+ or IHC score 2+, without gene amplification) tumors is challenged by methodological and analytical variables that might influence the sensitivity and reproducibility of HER2 testing. To open all possible therapeutic opportunities for HER2-low breast cancer patients the implementation of more accurate and reproducible testing strategies is mandatory. Here, we provide an overview of the existing barriers that may trouble HER2-low identification in breast cancer and discuss practical solutions that could enhance HER-low assessment.